Electrode for lithium ion battery and lithium ion battery

By using sulfonic acid compound and LizNi(1-x-y)CoxMyO2 composition on the electrode of the lithium-ion battery, a stable SEI coating was formed, which solved the problem of electrolyte decomposition in repeated charge and discharge of the lithium-ion battery, and achieved high capacity and low capacity The maintenance of resistance improves the cycle and storage characteristics of the battery.

CN119256410APending Publication Date: 2025-01-03SUMITOMO SEIKA CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380042491.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the repeated charging and discharging process of lithium-ion batteries, lithium loss is caused by the decomposition of the electrolyte on the electrode surface, resulting in a decrease in battery capacity. The prior art is difficult to effectively prevent the electrolyte on the electrode surface from decomposing the electrolyte on the electrode surface, affecting the cycle characteristics and storage characteristics of the battery.

Method used

The electrode for a lithium-ion battery containing a sulfonic acid compound is adopted. The sulfonic acid compound is composed of sulfonic acid anion and Ni cation, combined with LizNi(1-x-y)CoxMyO2 as the positive electrode active substance, and adhered to the electrode surface by impregnation method to form a stable SEI coating is used to inhibit electrolyte decomposition.

Benefits of technology

It effectively suppresses the rise in resistance of lithium-ion batteries when they are repeatedly charged and discharged at high temperatures, maintains high capacity, and improves the cycle stability and resistance reduction of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256410A_ABST
    Figure CN119256410A_ABST
Patent Text Reader

Abstract

An electrode for a lithium ion battery, which contains a sulfonic acid compound that contains a sulfonic acid anion represented by formula (1) and an Ni cation (R-SO3-(1) wherein R represents a hydrogen atom, and R represents a hydrogen atom, and R represents a hydrogen atom; in the present invention, R represents an alkyl group having 1-5 carbon atoms, which may be substituted by a fluorine atom, an alkenyl group having 2-5 carbon atoms, which may be substituted by a fluorine atom, an alkynyl group having 2-5 carbon atoms, which may be substituted by a fluorine atom, or an aryl group, which may be substituted by a fluorine atom, the positive electrode has a positive electrode active material layer, and the positive electrode active material layer contains LizNi (1-x-y) CoxMyO2 as a positive electrode active material, 0 < = x < = 0.40, 0 < = y < = 0.40, and 0.90 < = z < = 1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb, and Al.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrode for a lithium ion battery and a lithium ion battery. Background Art

[0002] In lithium-ion batteries, when repeatedly charged and discharged, lithium loss occurs due to the decomposition of the electrolyte on the electrode surface, and as a result, there is a tendency for the capacity of the battery to decrease. Therefore, as a method for preventing the decomposition of the electrolyte on the electrode surface, a method for forming a film on the electrode surface is being studied. For example, in Patent Document 1, it is recorded that in order to improve the cycle characteristics and storage characteristics, a specific lithium sulfonate salt is added to the negative electrode slurry and dispersed, the slurry is applied and dried, so that the lithium sulfonate salt is attached to the surface of the negative electrode active material. In addition, in Patent Document 2, it is recorded that in order to reduce the battery resistance after storage, a battery containing LiPF6 and lithium bis(fluorosulfonyl)imide (LiFSI) as electrolytes and a non-aqueous electrolyte of lithium trifluoromethylsulfonate as an additive is used.

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2014 / 119375

[0006] Patent Document 2: International Publication No. 2020 / 026853 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] The present invention relates to an electrode for a lithium ion battery capable of maintaining a high capacity when the lithium ion battery is repeatedly charged and discharged at a high temperature.

[0009] Means for solving technical problems

[0010] One aspect of the present invention relates to an electrode for a lithium ion battery, comprising a sulfonic acid compound, wherein the sulfonic acid compound comprises a sulfonic acid anion represented by the following formula (1) and a Ni cation,

[0011] R-SO3 - (1)

[0012] In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

[0013] One aspect of the electrode has a positive electrode active material layer, the positive electrode active material layer comprising LizNi (1-x-y)CoxMyO2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al) is used as the positive electrode active material.

[0014] Another aspect of the electrode is used as a negative electrode of a lithium ion battery having a positive electrode and a negative electrode disposed opposite to each other and an electrolyte, wherein the positive electrode has a positive electrode active material layer, and the positive electrode active material layer contains LizNi (1-x-y) CoxMyO2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al) is used as the positive electrode active material.

[0015] Another aspect of the present invention relates to a lithium ion battery comprising a positive electrode and a negative electrode disposed opposite to each other and an electrolyte, wherein at least one of the positive electrode or the negative electrode contains a sulfonic acid compound containing a sulfonic acid anion represented by the following formula (1) and a Ni cation.

[0016] R-SO3 - (1)

[0017] In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

[0018] In the above lithium-ion battery, the positive electrode has a positive electrode active material layer, and the positive electrode active material layer contains LizNi (1-x-y) CoxMyO2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al) is used as the positive electrode active material.

[0019] Effects of the Invention

[0020] According to one aspect of the present invention, there is provided an electrode for a lithium ion battery capable of maintaining a high capacity when the lithium ion battery is repeatedly charged and discharged at a high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a cross-sectional view showing an example of an electrode for a lithium ion battery.

[0022] Figure 2 It is a cross-sectional view showing an example of a lithium ion battery. DETAILED DESCRIPTION

[0023] Several embodiments of the present invention will be described in detail. The present invention is not limited to the following examples.

[0024] Figure 1 It is a cross-sectional view schematically showing an example of an electrode for a lithium ion battery. Figure 1 The lithium ion battery electrode 10 shown in FIG. 1 includes a current collector 11 and an active material layer 12. Figure 1 As shown, active material layer 12 may be provided on one surface of current collector 11 or on both surfaces of current collector 11 .

[0025] An example of the lithium ion battery electrode 10 includes a sulfonic acid compound including a sulfonic acid anion represented by the following formula (1) and a Ni cation.

[0026] R-SO3 - (1)

[0027] In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

[0028] When the lithium ion battery electrode 10 contains a sulfonic acid compound containing a sulfonic acid anion represented by formula (1) and a Ni cation, the decomposition of the electrolyte on the surface of the lithium ion battery electrode 10 can be suppressed in a lithium ion battery produced using the lithium ion battery electrode 10, compared with a case where the sulfonic acid compound is not contained. This is believed to contribute to suppressing the increase in resistance and maintaining a high capacity when the lithium ion battery is repeatedly charged and discharged.

[0029] The alkyl group, alkenyl group, alkynyl group and aryl group as R may be unsubstituted, and one or more hydrogen atoms may be substituted by fluorine atoms.

[0030] The number of carbon atoms of the alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom is 1, 2, 3, 4 or 5. The alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom may be a straight chain or a branched chain. Examples of the alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group and a trifluoromethyl group. From the viewpoint of reducing battery resistance, the alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom may be a methyl group, an ethyl group or a tert-butyl group. When the alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom is a methyl group which may be substituted with a fluorine atom, the battery resistance can be further reduced.

[0031] The number of carbon atoms of the alkenyl group having 2 to 5 carbon atoms which may be substituted with a fluorine atom is 2, 3, 4 or 5. The alkenyl group having 2 to 5 carbon atoms which may be substituted with a fluorine atom may be straight-chain or branched. Examples of the alkenyl group having 2 to 5 carbon atoms which may be substituted with a fluorine atom include vinyl, allyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, isobutenyl and 1,1-difluoro-1-propenyl. The alkenyl group having 2 to 5 carbon atoms which may be substituted with a fluorine atom may be vinyl which may be substituted with a fluorine atom.

[0032] The number of carbon atoms of the alkynyl group having 2 to 5 carbon atoms which may be substituted by a fluorine atom is 2, 3, 4 or 5. The alkynyl group having 2 to 5 carbon atoms which may be substituted by a fluorine atom may be straight-chain or branched. Examples of the alkynyl group having 2 to 5 carbon atoms which may be substituted by a fluorine atom include 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl and 3-butynyl. The alkynyl group having 2 to 5 carbon atoms which may be substituted by a fluorine atom may be 2-propynyl which may be substituted by a fluorine atom.

[0033] Examples of the aryl group which may be substituted with a fluorine atom include a phenyl group, a tolyl group, a pentafluorophenyl group, a xylyl group and a naphthyl group.

[0034] The Ni cation may be a divalent, trivalent, or tetravalent Ni cation. From the viewpoint of further suppressing an increase in resistance and a decrease in capacity when the lithium ion battery is repeatedly charged and discharged, the Ni cation may be a divalent Ni cation.

[0035] The sulfonic acid compound may be a compound represented by the following formula (2).

[0036] (R-SO3 - )2[Ni] 2+ (2)

[0037] R in formula (2) has the same meaning as R in the above formula (1).

[0038] Examples of the compound represented by the above formula (2) include nickel (II) methanesulfonate, nickel (II) trifluoromethanesulfonate, nickel (II) ethanesulfonate, nickel (II) propanesulfonate, nickel (II) pentanesulfonate, nickel (II) vinylsulfonate, nickel (II) allylsulfonate, nickel (II) propynylsulfonate, nickel (II) benzenesulfonate and nickel (II) pentafluorobenzenesulfonate.

[0039] The sulfonic acid compound may be attached to the surface of the lithium ion battery electrode 10 . More specifically, the sulfonic acid compound may be attached to the surface of the active material layer 12 .

[0040] As a method for attaching the sulfonic acid compound to the surface of the active material layer 12, for example, a method including a step of immersing the electrode for lithium ion battery in a solution containing the above-mentioned sulfonic acid compound can be cited. The immersion time can be, for example, less than 48 hours or less than 24 hours, or can be more than 1 hour. In addition, the temperature of the solution for immersing the electrode can be, for example, room temperature (25° C.) to 40° C. The solution containing the sulfonic acid compound can be an electrolyte in a lithium ion battery.

[0041] It is known that in lithium-ion batteries, an electrochemical reaction occurs on the electrode surface during initial charge and discharge, and a film called a solid electrolyte interface (SEI) (hereinafter also referred to as "SEI film") is formed on the surface of the active material layer, etc. The lithium-ion battery electrode 10 may have an SEI film, and more specifically, may have an SEI film formed on the surface of the active material layer 12. In this case, the sulfonic acid compound may be contained in the SEI film.

[0042] The lithium ion battery electrode 10 is an electrode for a lithium ion battery, and may be a positive electrode or a negative electrode. When the lithium ion battery electrode 10 is a positive electrode for a lithium ion battery, the current collector 11 is a positive electrode current collector, and the active material layer 12 is a positive electrode active material layer. Furthermore, when the lithium ion battery electrode 10 is a negative electrode for a lithium ion battery, the current collector 11 is a negative electrode current collector, and the active material layer 12 is a negative electrode active material layer.

[0043] The positive electrode collector may include a material with electronic conductivity. As an example of a material with electronic conductivity, conductive materials such as carbon, titanium, chromium, molybdenum, ruthenium, rhodium, tantalum, tungsten, osmium, iridium, platinum, gold, aluminum, and alloys containing two or more conductive materials (e.g., stainless steel) can be cited. From the viewpoint of high electronic conductivity, stability in the electrolyte and excellent oxidation resistance, the material of the positive electrode collector may be carbon, aluminum or stainless steel, and from the viewpoint of cost, may be aluminum.

[0044] The positive electrode current collector may be a foil (foil-shaped). When the positive electrode current collector is a foil, the positive electrode current collector may have a primer layer on its surface from the viewpoint of achieving a higher capacity.

[0045] The positive electrode active material layer contains a positive electrode active material. The positive electrode active material may be a lithium-containing composite oxide. Examples of lithium-containing composite oxides include LiMnO2, LiFeO2, LiMn2O4, Li2FeSiO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、Li z Ni (1-x-y) Co x M y O2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al.), LiFePO4, and Li z Co (1-x) M x O2 (wherein 0≤x≤0.1 and 0.97≤z≤1.20, M is at least one element selected from the group consisting of Mn, Ni, V, Mg, Mo, Nb and Al.) From the perspective of further achieving a high capacity of the battery, the positive electrode active material may be LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 or Li z Ni (1-x-y) Co x M y O2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al.).

[0046] From the viewpoint of easily maintaining the capacity of the lithium ion battery at a higher level, the positive electrode active material layer may contain Li z Ni (1-x-y) Co x M y O2 (wherein 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al) is used as a positive electrode active material.

[0047] The negative electrode current collector may include, for example, a metal such as aluminum, copper, nickel, and stainless steel. From the perspective of ease of processing and cost, the negative electrode current collector may include copper. The negative electrode current collector may be a foil (foil-shaped). The surface of the negative electrode current collector may be roughened.

[0048] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material is, for example, a material that can absorb and release lithium. Examples of negative electrode active materials include carbon materials such as graphite and amorphous carbon, and oxide materials such as indium oxide, silicon oxide, tin oxide, lithium titanate, zinc oxide, and lithium oxide. In addition, the negative electrode active material may be lithium metal or a metal material that can form an alloy with lithium. Examples of metals that can form an alloy with lithium include Cu, Sn, Si, Co, Mn, Fe, Sb, and Ag. The negative electrode active material is an alloy containing these metals and lithium, and may also contain an alloy containing two or three metals. These exemplified negative electrode active materials may be used alone or in combination of two or more.

[0049] From the viewpoint of high energy density, the negative electrode active material may include carbon materials such as graphite and amorphous carbon and Si-based active materials selected from Si, Si alloys and Si oxides. In this case, the mass ratio of the Si-based active material relative to the total mass of the carbon material and the Si-based active material may be 0.5 mass %, 1 mass % or more, or 2 mass %, or less than 95 mass %, 50 mass % or less, or 40 mass %. The mass ratio of the Si-based active material relative to the total mass of the carbon material and the Si-based active material may be 0.5 mass % or more and 95 mass %, 50 mass % or less, or 40 mass %, or 1 mass % or more and 95 mass %, 50 mass % or less, or 40 mass %, or 2 mass % or more and 95 mass %, 50 mass % or less, or 40 mass %.

[0050] The positive electrode active material layer and the negative electrode active material layer may further include a binder. As examples of binders, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, styrene-butadiene copolymer rubber (SBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene, polypropylene, polyethylene, polyimide, polyamide-imide, polyacrylic acid, polyacrylic acid metal salt, polyvinyl alcohol, acrylic acid-polyacrylonitrile, polyacrylamide, polymethacrylic acid and their copolymers can be cited. The positive electrode active material layer and the negative electrode active material layer may include binders that are the same or different from each other. In the case where the positive electrode active material layer includes a binder, the binder included in the positive electrode active material layer may be polyvinylidene fluoride (PVDF). In the case where the negative electrode active material layer includes a binder, from the viewpoint of having better cycle characteristics, the binder included in the negative electrode active material layer may be SBR, CMC, polyacrylic acid or a copolymer containing them.

[0051] An example of a lithium ion battery comprises a positive electrode and a negative electrode disposed opposite to each other and an electrolyte, wherein at least one of the positive electrode and the negative electrode contains the above-mentioned sulfonic acid compound. The positive electrode and the negative electrode may be the above-mentioned electrodes for lithium ion batteries.

[0052] Figure 2 It is a cross-sectional view schematically showing an example of a lithium ion battery. Figure 2 The lithium ion battery 1 shown in FIG. 1 includes negative electrodes 4 and positive electrodes 9 alternately stacked, an electrolyte 5 disposed between the negative electrodes 4 and the positive electrodes 9, and a separator 6 disposed in the electrolyte 5. The lithium ion battery 1 includes 7 layers of negative electrodes 4 and 6 layers of positive electrodes 9. Figure 2 , a part of the repeated structure is omitted. The negative electrode 4 has a negative electrode collector 3 and a negative electrode active material layer 2 provided on both sides of the negative electrode collector 3. The positive electrode 9 has a positive electrode collector 8 and a positive electrode active material layer 7 provided on both sides of the positive electrode collector 8. The positive electrode 9 is a positive electrode for a lithium ion battery having the above-mentioned positive electrode collector and the positive electrode active material layer. In addition, the negative electrode 4 is a negative electrode for a lithium ion battery having the above-mentioned negative electrode collector and the negative electrode active material layer.

[0053] The electrolyte 5 specifically contains a non-aqueous solvent and an electrolyte. The electrolyte 5 may be a non-aqueous electrolyte.

[0054] From the viewpoint that the viscosity of electrolyte 5 is suppressed to be lower, nonaqueous solvent can be an aprotic solvent.Aprotic solvent can be at least one selected from the group consisting of cyclic carbonate, linear carbonate, aliphatic carboxylic acid ester, lactone, lactam, cyclic ether, linear ether, sulfone, nitrile and these halogen derivatives.Aprotic solvent can comprise cyclic carbonate or linear carbonate, can comprise the combination of cyclic carbonate and linear carbonate.

[0055] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, and fluoroethylene carbonate. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of aliphatic carboxylic acid esters include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, and methyl trimethylacetate. Examples of lactones include γ-butyrolactone. Examples of lactams include ε-caprolactam and N-methylpyrrolidone. Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, and 1,3-dioxolane. Examples of chain ethers include 1,2-diethoxyethane and ethoxymethoxyethane. Examples of sulfones include sulfolane. Examples of nitrites include acetonitrile. Examples of halogen derivatives include 4-fluoro-1,3-dioxolane-2-one, 4-chloro-1,3-dioxolane-2-one, and 4,5-difluoro-1,3-dioxolane-2-one. The nonaqueous solvent may contain one or more compounds selected from these.

[0056] The content of the nonaqueous solvent in the electrolytic solution 5 is, for example, 70 to 99% by mass based on the total mass of the electrolytic solution 5 .

[0057] The electrolyte may be a lithium salt that is an ion source of lithium ions. The electrolyte may include at least one lithium salt (first lithium salt) selected from the group consisting of LiAlCl4, LiBF4, LiPF6, LiClO4, LiTFSI (lithium bistrifluoromethanesulfonyl imide), LiFSI (lithium bisfluorosulfonyl imide), LiAsF6 and LiSbF6. From the viewpoint of having a high degree of dissociation and being able to improve the ion conductivity of the electrolyte and further having the effect of suppressing the performance degradation of the storage device caused by long-term use through anti-oxidation-reduction characteristics, the electrolyte may include LiBF4, LiPF6 or a combination thereof.

[0058] When the electrolyte is LiBF4, LiPF6 or a combination thereof, the non-aqueous solvent may contain cyclic carbonate and chain carbonate. LiBF4 and / or LiPF6 may be combined with ethylene carbonate and diethyl carbonate.

[0059] The concentration of the electrolyte in the electrolyte 5 can be 0.1 mol / L or more and 2.0 mol / L or less, based on the total volume of the electrolyte 5. When the concentration of the electrolyte based on the total volume of the electrolyte 5 is 0.1 mol / L or more, it is easy to obtain good conductivity of the electrolyte 5, and when it is 2.0 mol / L or less, it is particularly easy to ensure the mobility of ions by suppressing the increase in the viscosity of the electrolyte 5. From the same point of view, the concentration of the electrolyte can be 0.5 mol / L or more, or 1.5 mol / L or less, based on the total volume of the electrolyte 5.

[0060] The electrolyte 5 may contain the above-mentioned lithium salt (first lithium salt) and one or more second lithium salts different from the first lithium salt. Examples of the second lithium salt include lithium difluorophosphate, lithium bis(oxalato)borate (LiBOB), lithium tetrafluoro(oxalate)phosphate (LiTFOP), lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalato)phosphate (LiDFOP), lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoro(oxalate)phosphate, and Li2PO3F, which have a phosphate skeleton, and lithium trifluoro((methylsulfonyl)oxy)borate, lithium pentafluoro((methylsulfonyl)oxy)phosphate, lithium methyl sulfate, lithium ethyl sulfate, 2,2,2-trifluoroethyl lithium sulfate, and lithium fluorosulfonate, which have a S(=O) group. The second lithium salt may include one or more lithium salts selected from the group consisting of lithium difluorophosphate, lithium bisoxalatoborate, lithium tetrafluoro(oxalate)phosphate, lithium difluorooxalatoborate, lithium difluorobisoxalatephosphate, lithium methylsulfate, lithium ethylsulfate, and lithium fluorosulfonate.

[0061] The concentration of the second lithium salt in the electrolyte 5 may be 1.0 mol / L or less based on the total volume of the electrolyte 5. When the concentration of the second lithium salt is 1.0 mol / L or less, the mobility of the ions can be sufficiently ensured because the viscosity of the electrolyte 5 is not easily increased. From the same point of view, the concentration of the second lithium salt may be 0.8 mol / L or less or 0.5 mol / L or less.

[0062] The electrolyte 5 may contain the above-mentioned sulfonic acid compound as an additive. When the electrolyte 5 contains the sulfonic acid compound, the sulfonic acid compound can be attached to the surface of the positive electrode active material layer 7 of the positive electrode 9 and / or the negative electrode active material layer 2 of the negative electrode 4 by immersing the positive electrode 9 and / or the negative electrode 4 (electrode for lithium ion battery) in the electrolyte 5. And, after the sulfonic acid compound is attached to the surface of the positive electrode active material layer 7 and / or the negative electrode active material layer 2, the lithium ion battery 1 is charged and discharged. When the SEI film is formed on the surface of the positive electrode active material layer 7 and / or the negative electrode active material layer 2, the formed SEI film can contain the sulfonic acid compound. The sulfonic acid compound can be attached only to the surface of either the positive electrode active material layer 7 or the negative electrode active material layer 2. From the viewpoint of further reducing the resistance, it can be attached to the surface of the positive electrode active material layer 7 and the negative electrode active material layer 2.

[0063] The concentration of the sulfonic acid compound in the electrolyte 5 may be 0.05 mmol / L or more, 0.1 mmol / L or more, or 0.2 mmol / L or more, based on the total amount of the electrolyte 5. Furthermore, the concentration of the sulfonic acid compound in the electrolyte 5 may be 0.05 mmol / L or more, 0.1 mmol / L or more, or 0.2 mmol / L or more and 1.0 mol / L or less, based on the total amount of the electrolyte 5.

[0064] The electrolyte 5 may contain a compound having a sulfonyl group (>S(=O)2) as an additive, which is different from the sulfonic acid compound of formula (1). Examples of the compound having the sulfonyl group include 1,3-propane sultone, 1-propylene 1,3-sultone, 1,3,2-dioxathiolane-2,2-dioxide, 1,3,2-dioxane-2,2-dioxide, 2-(methylsulfonyl)ethyl methanesulfonate, 2-(methylsulfonyl)ethyl ethanesulfonate, 2-(methylsulfonyl)ethyl vinylsulfonate, 2-(methylsulfonyl)ethylbenzenesulfonate, 3-trifluoromethylsulfonyltetrahydrothiophene-1,1-dioxide, 3-methylsulfonyltetrahydrothiophene-1,1-dioxide, 3-vinylsulfonyltetrahydrothiophene-1,1-dioxide, 3-methylallylsulfonate, 2-methyl-1-butylene ... Acyltetrahydrothiophene-1,1-dioxide, benzenesulfonyltetrahydrothiophene-1,1-dioxide, 3-methanesulfonyltetrahydrothiophene-1,1-dioxide-2-ene, 4-methanesulfonyltetrahydrothiophene-1,1-dioxide, 3-methanesulfonyloxytetrahydrothiophene-1,1-dioxide, 3-vinylsulfonyloxytetrahydrothiophene-1,1-dioxide, 3-methylallylsulfonyloxytetrahydrothiophene-1,1-dioxide, benzenesulfonyloxytetrahydrothiophene-1,1-dioxide, 3-methanesulfonyloxytetrahydrothiophene-1,1-dioxide-2-ene, 4-methanesulfonyloxytetrahydrothiophene-1,1-dioxide, and methylene methanedisulfonate. These compounds may be used alone or in combination of two or more. When the electrolyte 5 contains a compound having a sulfonyl group, when the lithium ion battery 1 is charged and discharged, the electrochemical reaction on the surface of the positive electrode active material layer 7 and / or the negative electrode active material layer 2 sometimes generates the above-mentioned sulfonic acid compound containing sulfonic acid anions and Ni cations from the compound having a sulfonyl group. In this case, an SEI film containing the sulfonic acid compound can be formed. The sulfonic acid compound can be attached only to the surface of either the positive electrode active material layer 7 or the negative electrode active material layer 2. From the perspective of further reducing the resistance, it can be attached to the surface of the positive electrode active material layer 7 and the negative electrode active material layer 2.

[0065] The concentration of the compound having a sulfonyl group in the electrolyte 5 is not particularly limited, but from an economical point of view, it may be 0.005 mass % or more, 0.01 mass % or more, or 0.05 mass % or more, based on the total mass of the electrolyte 5. The concentration of the compound having a sulfonyl group may be 0.005 mass % or more and 10 mass % or less, or 0.005 mass % or more and 5 mass % or less.

[0066] The electrolyte 5 may contain other additives different from the above-mentioned sulfonic acid compound and the compound having a sulfonyl group. As examples of other additives, compounds containing sulfur atoms other than the above-mentioned sulfonic acid compound and the compound having a sulfonyl group, negative electrode protective agents, positive electrode protective agents, flame retardants, overcharge inhibitors, cyclic carbonate compounds, nitrile compounds, isocyanate compounds, compounds having acetylene-1,2-diyl (-C≡C-), phosphate compounds, acid anhydrides, cyclic phosphazene compounds, compounds containing boron atoms, and compounds containing silicon atoms can be cited.

[0067] Examples of the compound containing a sulfur atom other than the sulfonic acid compound and the compound having a sulfonyl group include 1,3,2-dioxathiolane-oxide and 1,3,2-dioxane-2-oxide.

[0068] Examples of cyclic carbonate compounds include 4-fluoro-1,3-dioxolane-2-one (FEC), trans- or cis-4,5-difluoro-1,3-dioxolane-2-one (DFEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and 4-ethynyl-1,3-dioxolane-2-one (EEC). The cyclic carbonate compound may be VC, FEC, VEC, or a combination thereof.

[0069] Examples of nitrile compounds include mononitrile compounds such as acetonitrile and propionitrile, and dinitrile compounds such as succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, and sebaconitrile. The nitrile compound may be succinonitrile, adiponitrile, or a combination thereof.

[0070] Examples of the isocyanate compound include methyl isocyanate, ethyl isocyanate, butyl isocyanate, phenyl isocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, 1,4-phenylene diisocyanate, 2-isocyanatoethyl acrylate, and 2-isocyanatoethyl methacrylate.

[0071] Examples of compounds having an acetylene-1,2-diyl group (-C≡C-) include 2-propynyl methyl carbonate, 2-propynyl acetate, 2-propynyl formate, 2-propynyl methacrylate, di(2-propynyl) oxalate, methyl-2-propynyl oxalate, ethyl-2-propynyl oxalate, di(2-propynyl) glutarate, and dimethyl 2-butyne-1,4-dicarboxylate.

[0072] Examples of the phosphate ester compound include trimethyl phosphate, tributyl phosphate, trioctyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, bis(2,2,2-trifluoroethyl) ethyl phosphate, bis(2,2,2-trifluoroethyl) 2,2-difluoroethyl phosphate, bis(2,2,2-trifluoroethyl) 2,2,3,3-tetrafluoropropyl phosphate, bis(2,2-difluoroethyl) 2,2,2-trifluoroethyl phosphate, bis(2,2,3,3-tetrafluoropropyl) 2,2,2-trifluoroethyl phosphate, (2,2,2-trifluoroethyl) (2,2,3,3-tetrafluoropropyl) methyl phosphate, tris(1,1,1,3,3,3-hexafluoropropane-2-yl) phosphate, methyl methylenebisphosphonate, and methylenebisphosphonate. 2-(dimethylphosphoryl)acetate, ethyl 2-(dimethylphosphoryl)acetate, methyl 2-(diethylphosphoryl)acetate, ethyl 2-(diethylphosphoryl)acetate, 2-propynyl 2-(dimethylphosphoryl)acetate, 2-propynyl 2-(diethylphosphoryl)acetate, methyl 2-(dimethoxyphosphoryl)acetate, ethyl 2-(dimethoxyphosphoryl)acetate, methyl 2-(diethoxyphosphoryl)acetate, ethyl 2-(diethoxyphosphoryl)acetate, 2-propynyl 2-(dimethoxyphosphoryl)acetate, 2-propynyl 2-(diethoxyphosphoryl)acetate, methyl pyrophosphate and ethyl pyrophosphate.

[0073] Examples of the acid anhydride include acetic anhydride, propionic anhydride, succinic anhydride, maleic anhydride, 3-allylsuccinic anhydride, glutaric anhydride, and itaconic anhydride.

[0074] Examples of the cyclic phosphazene compound include methoxypentafluorocyclotriphosphazene, ethoxypentafluorocyclotriphosphazene, phenoxypentafluorocyclotriphosphazene, and ethoxyheptafluorocyclotetraphosphazene.

[0075] Examples of compounds containing a boron atom include boroxine, trimethylboroxine, trimethoxyboroxine, triethylboroxine, triethoxyboroxine, triisopropoxyboroxine, triisopropoxyboroxine, tri-n-propylboroxine, tri-n-propoxyboroxine, tri-n-butylboroxine, tri-n-butoxyboroxine, triphenylboroxine, triphenoxyboroxine, tricyclohexylboroxine and tricyclohexyloxyboroxine.

[0076] Examples of the compound containing a silicon atom include hexamethylcyclotrisiloxane, hexaethylcyclotrisiloxane, hexaphenylcyclotrisiloxane, 1,3,5-trimethyl-1,3,5-trivinylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, trimethylfluorosiloxane, triethylfluorosiloxane, tripropylfluorosiloxane, phenyldimethylfluorosiloxane, triphenylfluorosiloxane, vinyldimethylfluorosiloxane, vinyldiethylfluorosiloxane, vinyldiphenylfluorosiloxane, trimethoxyfluorosiloxane, triethoxyfluorosiloxane, dimethyldifluorosiloxane, diethyldifluorosiloxane, divinyldifluorosiloxane, and ethylvinyldifluorosiloxane. trimethylsilyl ester, trimethylsilyl acetate, triethylsilyl acetate, trimethylsilyl propionate, trimethylsilyl methacrylate, trimethylsilyl trifluoroacetate, tri(trimethylsilyl) boron, tri(trimethylsilyl) phosphate and tri(trimethylsilyl) phosphite.

[0077] The separator 6 may be, for example, a porous film or a nonwoven fabric. The separator 6 may contain a resin selected from polyethylene, polypropylene, and fluororesin, or may not contain a polymer electrolyte. The separator 6 may be a single layer or may have multiple layers.

[0078] The specific configurations of the shapes and thicknesses of the components constituting the lithium-ion battery can be appropriately set by a person skilled in the art. Figure 2 The implementation methods can be changed appropriately.

[0079] Example

[0080] Hereinafter, the present invention will be described in further detail with reference to the following examples, but the present invention is not limited to these examples.

[0081] 1. Experiment 1

[0082] 1-1. Production of lithium-ion batteries

[0083] <Example 1-1>

[0084] Battery component manufacturing

[0085] A positive electrode sheet (manufactured by Yamaya Co., Ltd.) containing a lithium-containing composite oxide and a negative electrode sheet (manufactured by Yamaya Co., Ltd.) containing graphite were prepared. The positive electrode sheet has an aluminum foil (thickness 20 μm) as a positive electrode current collector and a positive electrode active material layer formed on both sides thereof. The positive electrode active material layer contains a lithium-containing composite oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), carbon black (CB) and carbon (KS) as conductivity imparting agents, and polyvinylidene fluoride (PVDF) as a binder. The mass ratios are lithium-containing composite oxides: CB:KS:PVDF=92:2.5:2.5:3. The negative electrode sheet has a copper foil (thickness 10μm) as a negative electrode collector and a negative electrode active material layer formed on one side. The negative electrode active material layer contains graphite (Gr) as a negative electrode active material and sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as a binder. The mass ratios are Gr:CMC:SBR=98:1:1. The negative electrode sheets and the positive electrode sheets are alternately stacked via a separator formed of propylene to produce a battery element with a total of 13 layers, including 7 layers of negative electrode sheets and 6 layers of positive electrode sheets as electrodes.

[0086] Preparation of non-aqueous electrolyte

[0087] LiPF6 as an electrolyte was dissolved in a mixed non-aqueous solvent (manufactured by KISHIDA CHEMICAL Co., Ltd.) containing ethylene carbonate (EC) and diethyl carbonate (EMC) at a volume composition ratio of EC:EMC=30:70 to obtain a LiPF6 solution with a concentration of 1 mol / L. Nickel trifluoromethanesulfonate (II) (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the LiPF6 solution to prepare a non-aqueous electrolyte. The concentration of nickel trifluoromethanesulfonate (II) was 0.4 mmol / L based on the total amount of the non-aqueous electrolyte.

[0088] Lithium-ion battery manufacturing

[0089] The battery element prepared by the above method was inserted into a bag formed of a laminated film having aluminum (thickness 40 μm) and a resin layer covering both sides thereof, so that the ends of the positive electrode sheet and the negative electrode sheet protruded from the bag. In addition, the non-aqueous electrolyte prepared by the above method was added to the bag, and the electrodes were immersed in the non-aqueous electrolyte by standing at room temperature (27° C.) for 5 hours to obtain a lithium ion battery having an electrode (positive electrode sheet and negative electrode sheet) containing a positive electrode active material layer or a negative electrode active material layer attached with nickel (II) trifluoromethanesulfonate.

[0090] <Example 1-2>

[0091] A lithium ion battery was obtained in the same manner as in Example 1-1 except that nickel (II) benzenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added instead of nickel (II) trifluoromethanesulfonate so that the concentration based on the total amount of the nonaqueous electrolyte was 0.14 mmol / L when preparing the nonaqueous electrolyte.

[0092] <Comparative Example 1-1>

[0093] A nonaqueous electrolyte was prepared in the same manner as in Example 1-1, except that nickel (II) trifluoromethanesulfonate was not added when preparing the nonaqueous electrolyte, to obtain a lithium ion battery.

[0094] <Comparative Example 1-2>

[0095] A lithium ion battery was obtained in the same manner as in Example 1-1 except that lithium trifluoromethanesulfonate (manufactured by Aldrich) was added instead of nickel (II) trifluoromethanesulfonate to give a concentration of 0.4 mmol / L based on the total amount of the nonaqueous electrolyte when preparing the nonaqueous electrolyte.

[0096] <Comparative Examples 1-3>

[0097] A lithium ion battery was obtained in the same manner as in Comparative Example 1-2 except that the concentration of lithium trifluoromethanesulfonate in the nonaqueous electrolyte was set to 0.14 mmol / L based on the total amount of the nonaqueous electrolyte.

[0098] 1-2. Evaluation

[0099] After charging the lithium ion batteries obtained in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 at 25°C for 1 hour at a current equivalent to 0.1C, they were kept at 25°C for 10 hours. Thereafter, they were charged at a current equivalent to 0.1C for 5 hours and kept at 45°C for 24 hours. Next, at 25°C, they were discharged to 3V at a current equivalent to 0.1C, and then degassed. Next, the battery was aged by sequentially performing the following operations to stabilize it: charging to 4.2V at a current equivalent to 0.2C and discharging to 3V at a current equivalent to 0.2C for 3 cycles, charging to 4.2V at a current equivalent to 0.5C and discharging to 3.0V at a current equivalent to 0.5C for 3 cycles, and charging to 4.2V at a current equivalent to 1C and discharging to 3.0V at a current equivalent to 1C for 3 cycles. Thereafter, as the initial charge and discharge, charging and discharging were performed at a current equivalent to 2.0C. The discharge capacity observed during the initial charge and discharge is referred to as "initial capacity".

[0100] (Determination of initial DCR)

[0101] After the initial charge and discharge, the lithium-ion battery was charged to 50% of the initial capacity, and then discharged at -10°C at a current equivalent to 0.2C, and the change in battery voltage was observed. After that, it was left to stand for 10 minutes, and the current (discharge rate) during discharge was changed to 0.5C, 1.0C, and 2.0C, and the change in voltage during repeated charge and discharge was read, and the DCR (Ω) was calculated from the value as "initial DCR (Ω)". DCR is a value equivalent to the resistance value of the battery, and it can be considered that the lower the DCR value, the higher the output characteristics of the battery.

[0102] (Determination of DCR and discharge capacity retention rate after cycling)

[0103] Next, the lithium ion batteries of the embodiments and comparative examples for which the initial DCR was measured were subjected to a charge and discharge cycle test at 45° C. in which the charge rate was 2C, the discharge rate was 2C, the charge end voltage was 4.2 V, and the discharge end voltage was 3.0 V. The discharge capacity at the time of 400 cycles was defined as the “capacity after the cycle”.

[0104] After the charge and discharge cycle test, DCR was measured by the same method as described above (measurement of initial DCR) by repeatedly charging and discharging at 50% of the capacity after the cycle, and the value was defined as "DCR after the cycle (Ω)".

[0105] The initial DCR, the DCR after the cycles, and the discharge capacity retention rate of the lithium ion batteries of the examples and comparative examples are shown in Table 1. The “discharge capacity retention rate” in Table 1 is a value obtained by the following formula.

[0106] "Discharge capacity retention rate" = {(capacity after cycle) / (initial capacity)}×100

[0107] [Table 1]

[0108]

[0109] As shown in Table 1, in Examples 1-1 and 1-2 using electrodes containing a compound comprising a sulfonic acid anion represented by formula (1) and a Ni cation, the lithium ion battery maintained a high capacity in the cycle test at high temperature. In addition, it was confirmed that the increase in resistance value after the cycle test at high temperature was suppressed compared to Comparative Example 1-1.

[0110] 2. Experiment 2

[0111] 2-1. Production of lithium-ion batteries

[0112] <Example 2-1>

[0113] Coin-type battery manufacturing

[0114] A positive electrode sheet (manufactured by Yamaya Co., Ltd.) containing a lithium-containing composite oxide and a negative electrode sheet (manufactured by Yamaya Co., Ltd.) containing graphite were prepared. The positive electrode sheet has an aluminum foil (thickness 20 μm) as a positive electrode current collector and a positive electrode active material layer formed on both sides thereof. The positive electrode active material layer contains a lithium-containing composite oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), carbon black (CB) and carbon (KS) as conductivity imparting agents, and polyvinylidene fluoride (PVDF) as a binder. The mass ratios are lithium-containing composite oxide: CB:KS:PVDF = 92:2.5:2.5:3. The negative electrode sheet has a copper foil (thickness 10μm) as a negative electrode collector and a negative electrode active material layer formed on one side. The negative electrode active material layer contains graphite as a negative electrode active material and carboxymethyl cellulose and styrene butadiene rubber as a binder. The mass ratios are graphite: carboxymethyl cellulose: styrene butadiene rubber = 98:1:1. A coin-type battery (CR2032) was made using the above-mentioned positive and negative electrode sheets and a filter ("GA-100" manufactured by ADVANTEC CO., LTD.) as a separator.

[0115] Preparation of non-aqueous electrolyte

[0116] A nonaqueous electrolyte was prepared in the same manner as in Example 1-1 except that the concentration of nickel (II) trifluoromethanesulfonate in the nonaqueous electrolyte was 700 ppm (2.16 mmol / L) based on the total amount of the nonaqueous electrolyte.

[0117] Lithium-ion battery manufacturing

[0118] The prepared non-aqueous electrolyte was injected into a coin-type battery prepared by the above method, and the battery was left to stand at room temperature (27°C) for 5 hours to immerse the electrodes in the non-aqueous electrolyte, thereby obtaining a lithium-ion battery having electrodes (positive electrode sheet and negative electrode sheet) comprising a positive electrode active material layer or a negative electrode active material layer attached with nickel (II) trifluoromethanesulfonate.

[0119] <Comparative Example 2-1>

[0120] A nonaqueous electrolyte was prepared in the same manner as in Example 2-1, except that nickel (II) trifluoromethanesulfonate was not added when preparing the nonaqueous electrolyte, and a lithium ion battery was obtained.

[0121] <Reference Example 2-1>

[0122] A lithium ion battery was obtained in the same manner as in Example 2-1 except that the positive electrode sheet was changed to a positive electrode sheet containing LiFePO 4 (manufactured by Yamaya Corporation).

[0123] <Reference Example 2-2>

[0124] A nonaqueous electrolyte was prepared in the same manner as in Reference Example 2-1, except that nickel (II) trifluoromethanesulfonate was not added when preparing the nonaqueous electrolyte, to obtain a lithium ion battery.

[0125] 2-2. Evaluation

[0126] (Determination of discharge capacity maintenance rate)

[0127] At 25°C, for the lithium-ion batteries obtained in Example 2-1, Comparative Example 2-1, and Reference Examples 2-1 to 2-2, the operation of charging to 4.2V with a current equivalent to 0.2C and discharging to 3V with a current equivalent to 0.2C was repeated for 2 cycles. Next, at 25°C, a charge and discharge cycle test was performed in which the charge rate was 2C, the discharge rate was 2C, the charge end voltage was 4.2V, and the discharge end voltage was 3.0V, and the charge and discharge cycle was repeated for 400 cycles. Among them, for Reference Examples 2-1 to 2-2, the charge end voltage was set to 3.7V. The discharge capacity observed during the first charge and discharge in the charge and discharge cycle test was set as the "initial capacity", the discharge capacity after 400 cycles was set as the "post-cycle capacity", and the "discharge capacity retention rate" was calculated by the following formula. The results are shown in Table 2.

[0128] "Discharge capacity retention rate" = {(capacity after cycle) / (initial capacity)}×100

[0129] [Table 2]

[0130]

[0131] As shown in Table 2, LiNi 0.5 Co 0.2 Mn 0.3 When O2 is used as the positive electrode active material, the positive electrode and the negative electrode contain nickel (II) trifluoromethanesulfonate (Example 2-1) and the discharge capacity retention rate during the cycle test is high compared to when nickel (II) trifluoromethanesulfonate is not contained (Comparative Example 2-1), and the high capacity is maintained even after repeated severe tests of multiple charge and discharge. On the other hand, it is confirmed that when LiFePO4 is used as the positive electrode active material, the positive electrode and the negative electrode contain nickel (II) trifluoromethanesulfonate (Reference Example 2-1) and the discharge capacity retention rate in the cycle test is low compared to when nickel (II) trifluoromethanesulfonate is not contained (Reference Example 2-2), which has an opposite tendency to Example 2-1 and Comparative Example 2-1.

[0132] 3. Experiment 3

[0133] 3-1. Production of lithium-ion batteries

[0134] <Example 3-1>

[0135] Coin-type battery manufacturing

[0136] A positive electrode sheet (manufactured by Yamaya Co., Ltd.) containing a lithium-containing composite oxide and a negative electrode sheet (manufactured by Yamaya Co., Ltd.) containing graphite were prepared. The positive electrode sheet has an aluminum foil (thickness 20 μm) as a positive electrode current collector and a positive electrode active material layer formed on one side thereof. The positive electrode active material layer contains a lithium-containing composite oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), carbon black (CB) and carbon (KS) as conductivity imparting agents, and polyvinylidene fluoride (PVDF) as a binder. The mass ratios are lithium-containing composite oxide: CB:KS:PVDF = 92:2.5:2.5:3. The negative electrode sheet has a copper foil (thickness 10μm) as a negative electrode collector and a negative electrode active material layer formed on one side. The negative electrode active material layer contains graphite as a negative electrode active material and carboxymethyl cellulose and styrene butadiene rubber as a binder. The mass ratios are graphite: carboxymethyl cellulose: styrene butadiene rubber = 98:1:1. A coin-type battery (CR2032) was made using the above-mentioned positive and negative electrode sheets and a filter ("GA-100" manufactured by ADVANTEC CO., LTD.) as a separator.

[0137] Preparation of non-aqueous electrolyte

[0138] A nonaqueous electrolyte was prepared in the same manner as in Example 1-1 except that the concentration of nickel (II) trifluoromethanesulfonate in the nonaqueous electrolyte was 700 ppm (2.16 mmol / L) based on the total amount of the nonaqueous electrolyte.

[0139] Lithium-ion battery manufacturing

[0140] The prepared non-aqueous electrolyte was injected into a coin-type battery prepared by the above method, and the battery was left to stand at room temperature (27°C) for 5 hours to immerse the electrodes in the non-aqueous electrolyte, thereby obtaining a lithium-ion battery having electrodes (positive electrode sheet and negative electrode sheet) comprising a positive electrode active material layer or a negative electrode active material layer attached with nickel (II) trifluoromethanesulfonate.

[0141] <Comparative Example 3-1>

[0142] A nonaqueous electrolyte was prepared in the same manner as in Example 3-1, except that nickel (II) trifluoromethanesulfonate was not added when preparing the nonaqueous electrolyte, and a lithium ion battery was obtained.

[0143] <Reference Example 3-1>

[0144] A lithium ion battery was obtained in the same manner as in Example 3-1 except that the positive electrode sheet was changed to a positive electrode sheet containing LiFePO 4 (manufactured by Yamaya Corporation).

[0145] <Reference Example 3-2>

[0146] A nonaqueous electrolyte was prepared in the same manner as in Reference Example 3-2, except that nickel (II) trifluoromethanesulfonate was not added when preparing the nonaqueous electrolyte, to obtain a lithium ion battery.

[0147] 3-2. Evaluation

[0148] (Determination of discharge capacity maintenance rate)

[0149] At 25°C, for the lithium-ion batteries obtained in Example 3-1, Comparative Example 3-1, and Reference Examples 3-1 to 3-2, the operation of charging to 4.2V with a current equivalent to 0.2C and discharging to 3V with a current equivalent to 0.2C was repeated for 2 cycles. Next, at 45°C, a charge and discharge cycle test was carried out in which the charge rate was 2C, the discharge rate was 2C, the charge end voltage was 4.2V, and the discharge end voltage was 3.0V, and the charge and discharge cycle was repeated for 100 cycles. Among them, for Reference Examples 3-1 to 3-2, the charge end voltage was set to 3.7V. The discharge capacity observed during the first charge and discharge in the charge and discharge cycle test was set as the "initial capacity", the discharge capacity after 100 cycles was set as the "post-cycle capacity", and the "discharge capacity retention rate" was calculated by the following formula. The results are shown in Table 3.

[0150] "Discharge capacity retention rate" = {(capacity after cycle) / (initial capacity)}×100

[0151] [Table 3]

[0152]

[0153] As shown in Table 3, it was confirmed that LiNi 0.5 Co 0.2 Mn 0.3When O2 is used as the positive electrode active material, the positive electrode and the negative electrode contain nickel (II) trifluoromethanesulfonate (Example 3-1) and the discharge capacity maintenance rate during the cycle test is high compared to when nickel (II) trifluoromethanesulfonate is not contained (Comparative Example 3-2), and the high capacity is maintained even after a severe cycle test at high temperature. On the other hand, it is confirmed that when LiFePO4 is used as the positive electrode active material, the positive electrode and the negative electrode contain nickel (II) trifluoromethanesulfonate (Reference Example 3-1) and the discharge capacity maintenance rate in the cycle test is low compared to when nickel (II) trifluoromethanesulfonate is not contained (Reference Example 3-2), which has an opposite tendency to Example 3-1 and Comparative Example 3-1. In addition, in this test 3, the difference in the discharge capacity maintenance rate between Example 3-1 and Comparative Example 3-1 is 1%, which is slightly smaller than the difference between Example 1-1 and Comparative Example 1-1 in the above test 1. This is because the number of charge and discharge cycles in this test 3 is as few as 100 cycles.

[0154] Description of Reference Numerals

[0155] 10-Lithium ion battery electrode, 11-Current collector, 12-Active material layer, 1-Lithium ion battery, 2-Negative electrode active material layer, 3-Negative electrode collector, 4-Negative electrode, 5-Electrolyte, 6-Separator, 7-Positive electrode active material layer, 8-Positive electrode collector, 9-Positive electrode.

Claims

1. A lithium ion battery electrode comprising a sulfonic acid compound, wherein the sulfonic acid compound comprises a sulfonic acid anion represented by the following formula (1) and a Ni cation, <h2 style=";text-align:left;direction:ltr">R-SO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> (1) In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms, The electrode has a positive electrode active material layer, wherein the positive electrode active material layer contains Li z Ni (1-x-y) Co x M y O2 is used as the positive electrode active material, 0≤x≤0.40, 0≤y≤0.40, and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb, and Al.

2. A lithium ion battery electrode comprising a sulfonic acid compound, wherein the sulfonic acid compound comprises a sulfonic acid anion represented by the following formula (1) and a Ni cation, <h2 style=";text-align:left;direction:ltr">R-SO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> (1) In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms, The electrode is used as a negative electrode of a lithium ion battery having a positive electrode and a negative electrode arranged opposite to each other and an electrolyte. The positive electrode has a positive electrode active material layer, and the positive electrode active material layer contains Li z Ni( 1-x-y) Co x M y O2 is used as the positive electrode active material, 0≤x≤0.40, 0≤y≤0.40, and 0.90≤z≤1.20, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb, and Al.

3. The lithium ion battery electrode according to claim 1 or 2, wherein: The sulfonic acid compound is a compound represented by the following formula (2): (R-SO3 - )2[Ni] 2+ (2) In formula (2), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

4. The lithium ion battery electrode according to any one of claims 1 to 3, wherein R is an alkyl group having 1 to 5 carbon atoms which may be substituted with a fluorine atom.

5. A lithium ion battery comprising a positive electrode and a negative electrode arranged opposite to each other and an electrolyte, At least one of the positive electrode or the negative electrode includes a sulfonic acid compound, the sulfonic acid compound including a sulfonic acid anion represented by the following formula (1) and a Ni cation, The positive electrode has a positive electrode active material layer, and the positive electrode active material layer contains Li z Ni (1-x-y) Co x M y O2 is used as the positive electrode active material, 0≤x≤0.40, 0≤y≤0.40 and 0.90≤z≤1.20, M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb and Al, <h2 style=";text-align:left;direction:ltr">R-SO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> (1) In formula (1), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

6. The lithium ion battery electrode according to claim 5, wherein: The sulfonic acid compound is a compound represented by the following formula (2): (R-SO3 - )2[Ni] 2+ (2) In formula (2), R represents an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine atoms, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine atoms, or an aryl group which may be substituted with fluorine atoms.

Citation Information

Patent Citations

  • Negative electrode for rechargeable battery, method for producing same, and rechargeable battery using same

    WO2014119375A1

  • Non-aqueous electrolytic solution for batteries, and lithium secondary battery

    WO2020026853A1